Titan to Earth: We have touchdown - Abd Razak, Dzulkifli (2005)
As our eyes are fixed on the ground, mesmerised by the unfolding events following the recent tsunami, many would have missed an equally mesmerising event that took place in the outer space last week. The historic event occurred last Saturday evening, when an Europeanmade space probe, Huygens, landed on the surface of Saturn's largest moon Titan. The saucershaped probe completed its final hours of a 2.2 billionmile mission to Titan. Huygens detached from the Cassini spacecraft around Christmas Day and spun silently toward Titan. Cassini is expected to re main in orbit around Saturn until at least July 2008. The spacecraft crossed Saturn's rings in June 2004 and sent revealing photos of the rings composed primarily of hydrogen and helium.